Surfactants and Detergents Updates and New Insights - Kumar Dutta, Ashim (IntechOpen, 2022)
Surfactants are ubiquitous and have applications in diverse areas, including food, cosmetics, detergents, lubricants, enhanced oil recovery (EOR), and targeted drug delivery systems. Their wide diversity of applications owes to their unique structure, namely, a hydrophilic and a hydrophobic group present in the same molecule. Although most surfactants used industrially are synthetic, there is a growing need for natural surfactants, as the latter is obtainable from renewable sources and are less toxic and highly biodegradable in contrast to their synthetic counterparts. This book is a compilation of interesting articles by various experts that cover various applications of both synthetic and natural surfactants.